Challenges and Future Directions for Human-Drone Interaction Research: An Expert Perspective - Lingam, S.N.; Franssen, M.; Petermeijer, S.M.; Martens, M. (Taylor & Francis, 2024)
Drones are likely to enter social spaces in the foreseeable future. Novel Human-Drone Interactions (HDI) will foster beyond typical drone-operator interaction, posing new human factors challenges. However, the specific focus areas for HDI research remain unclear. This study conducts 11 expert interviews to identify potential use cases and human factors challenges for HDI in public spaces. Initial drone use cases include emergency response and delivery scenarios, where the general public may interact as recipients and bystanders, each posing unique challenges. Uncertainty, stemming from a lack of awareness, emerges as a significant human factors concern, impacting perceived risk. Addressing this uncertainty, especially in recipients, may involve refining drone behaviour, physical appearance, and interface design. The challenges identified in this study lay the groundwork for future HDI research in public spaces.